2020
DOI: 10.1371/journal.pone.0238254
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of alphaviral RNA:Protein complexes reveals conserved host-pathogen interactions

Abstract: The identification of host / pathogen interactions is essential to both understanding the molecular biology of infection and developing rational intervention strategies to overcome disease. Alphaviruses, such as Sindbis virus, Chikungunya virus, and Venezuelan Equine Encephalitis virus are medically relevant positive-sense RNA viruses. As such, they must interface with the host machinery to complete their infectious lifecycles. Nonetheless, exhaustive RNA:Protein interaction discovery approaches have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Abbreviations: 4SU, 4-thiouridine; ActD, actinomycin D; ChIRP-MS, comprehensive identification of RNA-binding proteins by mass spectrometry; CLAMP, crosslinkassisted messenger ribonucleoprotein purification; Fvo, flavopiridol; HyPR-MS, hybridization purification of RNAprotein complexes followed by mass spectrometry; mRNP, messenger ribonucleoprotein; RAP-MS, RNA antisense purification and quantitative mass spectrometry; SPRI, solid-phase reversible immobilisation; TUX-MS, thiouracil cross-linking mass spectrometry; VIR-CLASP, viral cross-linking and solid-phase purification; vRIC, viral RNA interactome capture. See also [25][26][27][40][41][42][43][44][45][46][50][51][52][53].…”
Section: The Importance Of Cellular Rna-binding Proteins In Virus Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abbreviations: 4SU, 4-thiouridine; ActD, actinomycin D; ChIRP-MS, comprehensive identification of RNA-binding proteins by mass spectrometry; CLAMP, crosslinkassisted messenger ribonucleoprotein purification; Fvo, flavopiridol; HyPR-MS, hybridization purification of RNAprotein complexes followed by mass spectrometry; mRNP, messenger ribonucleoprotein; RAP-MS, RNA antisense purification and quantitative mass spectrometry; SPRI, solid-phase reversible immobilisation; TUX-MS, thiouracil cross-linking mass spectrometry; VIR-CLASP, viral cross-linking and solid-phase purification; vRIC, viral RNA interactome capture. See also [25][26][27][40][41][42][43][44][45][46][50][51][52][53].…”
Section: The Importance Of Cellular Rna-binding Proteins In Virus Infectionmentioning
confidence: 99%
“…The use of high MOI is not amenable for all viruses and, in some cases, can alter the kinetics of infection [ 99 ]. Other methods, such as vRIC [ 26 ], TUX-MS [ 50 , 51 ], and CLAMP [ 52 , 53 ], combine 4SU RNA labelling with the use of an inhibitor of cellular transcription [actinomycin D (ActD) or flavopiridol (Fvo)] to study the interactions that vRNA establishes with the cell after the replication burst. Because the vRNA-dependent RNA polymerase (RDRP) is insensitive to these compounds, 4SU is mainly incorporated into nascent vRNAs.…”
Section: Approaches To Uncover the Viral Rna Interactomementioning
confidence: 99%
See 1 more Smart Citation
“…Using this labelled vRNA as a bait, VIR-CLASP revealed that the gRNA of alphaviruses establishes functionally important interactions with hundreds of cellular RBPs during the initial steps of infection (Kim et al, 2020). To profile how these protein-RNA interactions evolve in conditions where viral replication is already active, an alternative method named cross-link-assisted mRNP purification (CLASP) was developed (Gebhart et al, 2020;LaPointe et al, 2018). CLASP employs 4SU labelling of vRNA, followed by formaldehyde crosslinking, 4SU biotinylation and streptavidin purification coupled with proteomics (Gebhart et al, 2020;LaPointe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To profile how these protein-RNA interactions evolve in conditions where viral replication is already active, an alternative method named cross-link-assisted mRNP purification (CLASP) was developed (Gebhart et al, 2020;LaPointe et al, 2018). CLASP employs 4SU labelling of vRNA, followed by formaldehyde crosslinking, 4SU biotinylation and streptavidin purification coupled with proteomics (Gebhart et al, 2020;LaPointe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%